Project-Based Learning Governance on Natural Materials Improving the Creativity of Class VIII Students of SMP Negeri 1 Sigumpar - siagian, roy; Nathanael Sitanggang; M. Joharis Lubis (Universitas Nahdatul Ulama Surabaya, 2022)
This research is motivated by the low participation of students of SMP Negeri 1 Sigumpar in participating in scientific work competitions which are their own innovations. According to Bloom and Anderson's taxonomy, creative competence is very necessary for all students because by learning to make something from the materials around it, thinking construction is very important because children will be formed and more critical and innovative. Science, Technology, Engineering, and Mathematics (STEM)-based learning really needs to be empowered from an early age. This research was conducted at SMP N 1 Sigumpar with the aim of knowing whether the application of the project-based learning model in these subjects was effective. Nature can be a material for students' innovative work and improve student learning outcomes. This research method uses a quasi-experimental research design with a one group pretest – post-test design. Data collection methods used in this study was questionnaires, survey and observations in class VIII of 30 students. Data analysis was carried out descriptively and qualitatively. The results showed that project-based learning increased creativity and student learning outcomes. From the results of this study, the researchers found that project-based learning is very good to be applied in teaching students because based on students' experiences it increases the enthusiasm for learning.